Improving the Quality and Equity of Basic Education In Turkey : Challenges and Options - World Bank (Washington, DC, 2013)
Providing education for all has been a core objective of many governments since the launch of the Millennium Development Goals a decade ago. Basic education is the foundation of education and learning and, as such, is the point where Turkey started its push for education for all. This policy note is designed as an input for the discussion among stakeholders in Turkey on how to improve the quality and equity of basic education. The document provides an analysis and benchmarking of the performance of basic education in Turkey in each of these areas along with international evidence and a discussion of specific policy options. Although Turkey has significantly expanded access to education in the last decade, important challenges await on two interrelated fronts: quality and equity. Turkey's educational system is currently of low quality relative to the growth and competitiveness ambitions of the country and is also significantly more inequitable than other Organization for Economic Co-Operation and Development, or OECD countries.